Child-Centered Justice in Domestic Sexual Violence Cases: A Doctrinal Analysis of Supreme Court Decision No. 243 K/Pid.Sus/2020 - Widodo Ramadhana; Yohana Ayu Sartika Telaumbanua; Barryl Wilfred Joshua Rohtuahdo Purba; Ananda Safron (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2026)
Child sexual violence within the family presents a distinctive legal problem because the perpetrator may simultaneously occupy a position of trust, authority, and domestic power. This article examines Supreme Court Decision No. 243 K/Pid.Sus/2020 concerning sexual violence committed by a stepfather against his stepdaughter. The study uses doctrinal legal research with statutory, case, conceptual, and analytical approaches. Primary legal materials consist of the Supreme Court decision and relevant Indonesian legislation, while secondary materials include peer-reviewed scholarship on child sexual abuse, victimology, sentencing, and victim-centered justice. The analysis finds that the case demonstrates the importance of treating the child not merely as evidence in criminal proceedings but as a rights-bearing victim whose safety, dignity, recovery, and participation must inform judicial reasoning. The twelve-year imprisonment imposed in the case reflects recognition of the seriousness of repeated sexual violence within a domestic relationship. However, punishment alone does not exhaust the state's protection obligation. The contemporary legal framework, particularly the Child Protection Law and Law No. 12 of 2022 on Sexual Violence Crimes, requires a broader response encompassing confidentiality, psychosocial recovery, restitution, procedural protection, and prevention of secondary victimization. The article proposes a child-centered sentencing framework that connects accountability with victim recovery and institutional coordination.